The phenomenon of anhydrobiosis—structural and functional changes in yeast cells - Kieliszek, Marek (Applied microbiology and biotechnology, 2025)
Anhydrobiosis is a phenomenon that involves the ability of microorganisms to survive in an environment of virtually complete dehydration. Yeast cells in anhydrobiosis exhibit several structural and functional changes. Survival of such extreme environmental conditions while maintaining the viability of eukaryotic cells after rehydration is a subject of constant interest in the scientific community worldwide. This review article presents the most essential information discussing the effect of dehydration on several structural and functional changes occurring in yeast cell organelles. It is worth emphasizing that at the cellular level, in dehydration conditions, it is possible to observe the occurrence of processes responsible for cytoplasm condensation, cytoskeleton reorganization or changes in the structure of the cell membrane and individual organelles. In addition, protein aggregation and a reduction in metabolic activity also occur. The consequence of such processes is the inhibition of the cell cycle and a decrease in the activity of individual enzymes. One of the key mechanisms responsible for yeast defense against this phenomenon is the accumulation of protective substances. Understanding the functioning of complex adaptive mechanisms of yeast cells occurring in the state of anhydrobiosis will constitute an extension of the current knowledge in this scientific field. It is worth emphasizing that conducting future research on explaining the complex relationships that occur at the molecular level in the cytosol of yeast cells between individual organelles will provide new molecular clues covering the functioning of particular signaling pathways. At the same time, using knowledge from this technological sector will be an opportunity to develop innovative technologies in the field of designing yeast-derived products. Key points • Yeast cells exhibit significant structural and functional changes in the anhydrobiosis state. • Dehydration leads to cytoskeleton reorganization, membrane changes, and cytoplasmic condensation. • Anhydrobiosis leads to protein aggregation and reduced translation at the ribosome level in yeast.